2013
DOI: 10.1155/2013/905389
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Dense Pore Structure by Te Addition in Bi0.5Sb1.5Te3: An Approach to Minimize Lattice Thermal Conductivity

Abstract: We herein report the electronic and thermal transport properties of p-type Bi0.5Sb1.5Te3polycrystalline bulks with dense pore structure. Dense pore structure was fabricated by vaporization of residual Te during the pressureless annealing of spark plasma sintered bulks of Te coated Bi0.5Sb1.5Te3powders. The lattice thermal conductivity was effectively reduced to the value of 0.35 W m−1 K−1at 300 K mainly due to the phonon scattering by pores, while the power factor was not significantly affected. An enhancedZTo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The theoretical study indicated that an internal disordered surface of pores can produce strong phonon scattering, thus improving the zT compared to 100% dense compositions, which has been demonstrated by experiment results and theoretical modeling . It was suggested that micro/nanoporous materials have an improvement in the S value, caused by the energy filtering effect, while the carrier scattering at the pores will lead to the deterioration of σ . Pan et al reported that dislocations and clean GBs were formed by an unconventional melt-centrifugation process to construct a porous network of platelet-like structures (Figure d).…”
Section: The Minimization Of Lattice Thermal Conductivitymentioning
confidence: 85%
See 1 more Smart Citation
“…The theoretical study indicated that an internal disordered surface of pores can produce strong phonon scattering, thus improving the zT compared to 100% dense compositions, which has been demonstrated by experiment results and theoretical modeling . It was suggested that micro/nanoporous materials have an improvement in the S value, caused by the energy filtering effect, while the carrier scattering at the pores will lead to the deterioration of σ . Pan et al reported that dislocations and clean GBs were formed by an unconventional melt-centrifugation process to construct a porous network of platelet-like structures (Figure d).…”
Section: The Minimization Of Lattice Thermal Conductivitymentioning
confidence: 85%
“…182 It was suggested that micro/nanoporous materials have an improvement in the S value, caused by the energy filtering effect, while the carrier scattering at the pores will lead to the deterioration of σ. 183 Pan et al 180 reported that dislocations and clean GBs were formed by an unconventional melt-centrifugation process to construct a porous network of platelet-like structures (Figure 12d). These collective defects resulted in a ∼60% reduction in κ L compared to ZM samples (Figure 12e), while the carriers remained moderately mobile throughout the liquid-fused grains.…”
Section: Planar Defectsmentioning
confidence: 99%
“…2(b)-2(d). The formation of nanopores may originate from the sublimation of Te segregations during high-temperature solidification because of its high vapor pressure (723 K), [38] compared to other elements with high boiling point such as Sb (1860 K), Bi (2273 K), and Ga (2676 K). This result is consistent with the anomalous effect of Ga intercalation in lattice parameters caused by the intrinsic point defects, especially Te vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is relatively difficult to apply the low-dimensional Bi 2 Te 3 to commercial or industrial uses. For these applications, bulk-type materials are ideal, and researchers have therefore endeavored to develop Bi 2 Te 3 nanobulk materials. High thermoelectric properties have been often reported for p-type Bi 2 Te 3 , especially Bi x Sb 2– x Te 3 . Researchers have generally reported the maximum ZT values ranging from 1.2 to 1.4 at approximately 100 °C for Bi x Sb 2– x Te 3 in the bulk phase; to the best of our knowledge, the highest ZT value is ca. 1.86 (at 47 °C) that Kim et al recently achieved .…”
Section: Introductionmentioning
confidence: 96%